Bioelectrical impedance vector analysis and body composition in cervical spinal cord injury: A pilot study - Bauermann, Andreia; Costa e Silva, Anselmo de Athayde; Figueiredo, Flávia; Koury, Josely Correa (Frontiers in Nutrition, 2022)
Introduction Body composition assessment in cervical spinal cord injury (c-SCI) individuals is important to monitor the fat free-mass (FFM) loss, due to immobilization, or gain, due to exercise practice. Single frequency bioelectrical impedance analysis (SF-BIA) is low in cost, simple and easy. Objectives The aims of this study are: to evaluate the concordance between the FFM values obtained using dual X-ray absorptiometry (DXA) and the three SF-BIA previous predictive equations; and to test the applicability of the bioelectrical impedance vector analysis (BIVA). Methods Twenty-three c-SCI males were divided into two groups: Physically active (PA; n = 13; at least 150 min/week) and non-active individuals (NPA) and were assessed by DXA and SF-BIA simultaneously. Results FFM values were similar between groups PA and NPA. Considering all participants, FFM values obtained by Kocina and Heyward (>11%) and Sun (<15.4%) predictive equations were different when compared to DXA (p < 0.01). However, Buchholz's et al. predictive equation showed FFM values similar to DXA, but presented poor concordance (<7%, p = 0.99; concordance coefficient = 0.85). BIVA showed consistency in ellipse distribution using FFM obtained using Buchholz et al. predictive equation. Conclusions The use of non-specific BIA equations can lead to misinterpretation in FFM values in male c-SCI individuals. Predictive equations for this group need to be developed.